Assessment of soluble skin surface protein levels for monitoring psoriasis vulgaris in adult psoriasis patients using non-invasive transdermal analysis patch: A pilot study - Orro, Kadri; Salk, Kristiina; Abram, Kristi; Arshavskaja, Jelena; Meikas, Anne; Karelson, Maire; Neuman, Toomas; Kingo, Külli; Spee, Pieter (Frontiers in Medicine, 2023)
To improve the care of patients with chronic inflammatory skin conditions, such as psoriasis, there is a need for diagnostic methods that can facilitate personalized medicine. This exploratory pilot study aimed to determine whether non-invasive measurements of inflammation-related proteins from psoriatic skin can be sampled using the FibroTx Transdermal Analysis Patch (TAP) to assess disease severity and monitor pharmacodynamic changes. Ten healthy volunteers and 44 psoriasis vulgaris patients were enrolled in the exploratory pilot study. Skin surface protein measurements for healthy and lesional skin were performed using TAP. Patients’ scores of psoriasis activity and severity (PASI) were documented, and differences in the thickness of skin layers were determined using sonography. The study assessed the skin surface protein levels of psoriasis patients undergoing whole-body treatment with narrow-band UVB to evaluate whether the levels of the skin surface proteins IL-1α, IL-1RA CXCL-1/2, and hBD-1 were associated with the disease activity and severity measurements. Using TAP technology, it was observed that there were clear differences in levels of IL-1α, IL-1RA, CXCL-1/2, and hBD-1 between psoriasis lesional and non-lesional skin. In addition, a positive correlation between CXCL-1/2 and desquamation, and between CXCL-1/2 and SLEB thickness was observed. During UVB treatment, the TAP measurements revealed a clear reduction of IL-1RA, CXCL 1/2, and hBD-1 on lesional skin. Further, skin surface measurements of IL-1RA and CXCL-1/2 displayed a different profile than those achieved by visual scoring of local inflammation, thus indicating that measuring the ‘molecular root’ of inflammation appears to have value as an objective, non-invasive biomarker measurement for scoring disease severity.